2013
DOI: 10.4028/www.scientific.net/msf.750.56
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cu Nanowires and its Effect on Proliferation of Mesenchymal Stem Cells

Abstract: Many studies have focused on the fabrication of Cu nanowires, because of their potential applications in diverse fields such as nanoelectronics and gene delivery. In this study, we successfully fabricated Cu nanowires by electrochemical deposition method. Cu nanowires was synthesized by electroplating from a 0.4M CuSO4 bath, and the current was 0.005A. The length of nanowires can be controlled via deposition time and current. After depositing for 60 minutes, the length of the nanowires is approximately 10 µm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Cytotoxicity studies of NWs have shown a dependence on factors like material and size. A high concentration of NWs might produce very low toxicity and good biocompatibility in some cell lines such as HeLa cells [34] , 3T3 fibroblasts (CRL-1658) [11] and L929 mouse fibroblast [20] , while being highly toxic for other cell lines including mesenchymal stem cells [35] and human colorectal carcinoma cells (HCT 116) [28] . These results together with other contributions have made Ni NWs very interesting for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity studies of NWs have shown a dependence on factors like material and size. A high concentration of NWs might produce very low toxicity and good biocompatibility in some cell lines such as HeLa cells [34] , 3T3 fibroblasts (CRL-1658) [11] and L929 mouse fibroblast [20] , while being highly toxic for other cell lines including mesenchymal stem cells [35] and human colorectal carcinoma cells (HCT 116) [28] . These results together with other contributions have made Ni NWs very interesting for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%